Understanding Needs, Breaking Down Barriers: Examining Mental Health Challenges and Well-Being of Correctional Staff in Ontario, Canada - Ricciardelli, Rosemary; Carleton, R. N.; Gacek, James; Groll, Dianne L. (Frontiers in Psychology, 2020)
Mental health challenges appear to be extremely problematic among correctional service employees, affecting persons working in community, institutional, and administrative correctional services. Focusing specifically on giving voice to correctional workers employed by the Ontario Ministry of Community Services and Corrections, we shed light on their interpretations of the complexities of their occupational work and of how their work affects staff. We show that participants encounter barriers to treatment seeking, which they describe as tremendous, starting with benefits, wages, and shift work. We let the voices of staff elucidate what is needed to create a healthier correctional workforce. Recommendations include more training opportunities and programs; quarterly, semi-annual, or annual appointments with a mental health professional who can assess changes in the mental health status of employees; off-site assessments to ensure confidentiality; and team building opportunities to reduce inter-personal conflict at work and increase moral by improving the work environment.